DIVERSIFIKASI â€œTUMERIC JUICEâ€ - Puspadewi, Kadek Rahayu; Budiningsih, Desak Nyoman; Susrawan, I Nyoman Adi (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2018)
The main purpose of this community service program is to optimize the marketing and diversification of jamu products. Jamu is a herb derived from natural herbs formulated without using chemicals as additives. Tumeric Juice is a traditional jamuthat using turmeric as its main material. In the management of tumeric juice still facing several problems, namely: 1) the limited gas stove so that the gas stove for business is used together for household purposes, 2) the limited capacity of the blender machine to smooth the raw materials, 3) the marketing is not yet optimal that is only for foreign tourists alone and only 1 type of jamu, and 4) does not have a monthly cashbook cash so that cash flow becomes unclear. To overcome these problems required transfer of technology through mentoring activities, counseling, and training. From the activities that have been done, 1) the existence of a special gas stove for the business, 2) the existence of a blender machine with a capacity of 1 kg, 3) the marketing of jamu is not only for foreign tourists but also for local communities, 4) there are three types ofjamu products, namely piduh, sambiroto, and temulawak and 5) the existence of cash book finance.